Pembelajaran E-Learning sebagai Upaya Meningkatkan Kemandirian Belajar Mahasiswa PGSD - suyanti suyanti (Jurnal Bidang Pendidikan Dasar, 2021)
This study has the aim of increasing student learning independence by learning E-Learning. Researchers in their method use PTK (Classroom Action Research), consisting of three cycles. The research subjects were 1st semester students of the basic concepts of social studies at SD PGSD PGRI Madiun University. The analysis used in this study uses descriptive analysis techniques. The results showed that there was an increase in student learning independence accompanied by an increase in student learning outcomes in the first cycle, namely 20 students (72%) to the second cycle, namely 21 students (74.5%), then in the third cycle there was an increase of 28 students (89%) who had already achieve mastery learning scores.